TINJAUAN TENTANG MAKANAN ADAT YANG DIBAWA PADA ACARA BABAKO DI NAGARI PAKAN RABAA - Erlina, Rini; Baidar, Baidar; Elida, Elida (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose study was (1) to describe the implementation of a series ofceremonies babako, (2) identify the types of traditional food, (3) describe theequipment used to carry food customs, (4) to know procedure of serving andstructuring, (5) expresses the meaning of traditional food that was brought to theceremony babako. This research descriptive qualitative, the object of studycustomary food babako ceremony . The technique of collecting data: observation,interview, and documentation. Data analysis tecniques: data reduction, datapresentation and conclusion of verification. The results showed that babakoceremony consists namely preparation before the event and the circuitimplementation babako. Food bronght totaling eleven types, and tool to bringtraditional food at a ceremony babako is a dulang, baki, toples, cambuang, kainrendo, dan kain pambungkui.The procedure of serving and structuring food that isbrought dulang and baki in the main house of induak bako then it taken to the nextthe anak daro taken to the marapulai home with a procession. Traditional food atceremony babako has the meaning of moral messages and life with anak darofamily and marapulai.Keyword: Traditional food, Ivent Babako